Ukuran Perusahaan, Good Corporate Governance, Eco-Control dan Luas Pengungkapan Corporate Social Responsibilty - Kusumaputri, Nengah Saraswati; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 31 No 7 (2021), 2021)
In recent years, corporate social responsibility or commonly known as corporate social responsibility (CSR) has become a major development issue for a company. In carrying out its activities, the company is inseparable from the environment and society. Companies that have the desire to survive and have a competitive advantage need to make CSR as one of their business strategies. Knowing how company size, GCG, and eco-control influence the extent of CSR disclosure is the aim of this study. The population used in this study is a number of companies listed on the IDX for the 2017-2019 period and including companies in the raw material producing sector. The sample used was 11 companies through purposive sampling method. This study uses multiple linear regression analysis techniques. The results of the study that can be drawn from this study, company size, GCG, and eco-control have an influence on the extent of CSR disclosure. Keywords: Extent Of Corporate Social Responsibility Disclosure; Company Size; Good Corporate Governance; Eco-Control.